Boosting Student Learning Motivation Through Project-Based Learning with Attention, Relevance, Confidence, and Satisfaction Motivational Design Process - Barlian, Yelly Andriani; Nurbani, Sri; Wijayanto, Pikir Wisnu (Jurnal Pendidikan Progresif, 2022)
Boosting Student Engagement Through Project-Based Learning with Attention, Relevance, Confidence, and Satisfaction Motivational Design Process. Objectives: This research aims to boost the students' writing ability and motivation by changing the teaching methods from classical (lectures and discussions) towards student activity. Methods: The method used in this study was the Project-Based Learning (PJBL) model with Attention, Relevance, Confidence, and Satisfaction (ARCS) motivational design. The case study used observation, questionnaires, and interviews in two stages of [A1] [p2] data collection for a English course class, namely English for Art and Design in the Visual Communication Design Study Program. The case study conducted from the beginning to the end of learning was carried out for one semester. Findings: By implementing the Project-Based learning method with ARCS motivational design, it is found that student motivation in the Attention, Relevance, and Satisfaction aspects is at a high level. Meanwhile, the Confidence aspect remains neutral in stages I and II. Conclusion: The achievement of this research in terms of increasing students' writing skills and motivation has been accomplished. Keywords: project-based learning, attention, relevance, confidence, and satisfaction, case study.DOI: http://dx.doi.org/10.23960/jpp.v12.i1.202216